2020
DOI: 10.1111/add.15042
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bottle size on in‐home consumption of wine: a randomized controlled cross‐over trial

Abstract: Aim To assess the impact of purchasing wine in 50 cl bottles compared with 75 cl bottles on the amount of wine consumed at home. Design Cross‐over randomized controlled trial with a ‘usual behaviour’ period of a maximum of 3 weeks between conditions. Setting Households in the United Kingdom. Participants One hundred and eighty‐six households that consumed between two and eight 75 cl bottles of wine each week. Intervention Households were randomized to the order in which they purchased wine in two bottle sizes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 25 publications
4
29
1
Order By: Relevance
“…Finally, there was no effect of bottle size on pouring behaviour, which was not in line with the study hypothesis that larger bottles increase the volume poured. This hypothesis was, however, based on just one previous study [ 21 ] which found that wine consumption was higher from 75 cl bottles, compared to 50 cl bottles. The mechanisms for this effect are unknown but one possibility is that it may reflect the tendency for people to consume in ‘units’ [ 33 ], with one bottle—regardless of size—comprising one unit.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Finally, there was no effect of bottle size on pouring behaviour, which was not in line with the study hypothesis that larger bottles increase the volume poured. This hypothesis was, however, based on just one previous study [ 21 ] which found that wine consumption was higher from 75 cl bottles, compared to 50 cl bottles. The mechanisms for this effect are unknown but one possibility is that it may reflect the tendency for people to consume in ‘units’ [ 33 ], with one bottle—regardless of size—comprising one unit.…”
Section: Discussionmentioning
confidence: 97%
“…Two wine bottle sizes were used in the study: (i) 50 cl, (ii) 75 cl. The set of bottle sizes was informed by a recent randomised controlled trial assessing the impact of bottle size on wine consumption [ 21 ]. Both bottles contained the same wine, using a branded bottle to increase ecological validity (Isla Negra Sauvignon Blanc: 13.2% alcohol by volume (abv)).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not specifically look at bottle size impact, but research has shown that large bottle sizes (i.e., 750 mL vs. 500 mL) increase consumption amount and drinking speed for wine [95]. However reduction of bottle size beyond a certain threshold may be counterproductive as people may end up consuming more bottles out of convenience and portability, amongst other reasons [96].…”
Section: Strengths and Limitations Of This Reviewmentioning
confidence: 99%
“…For example, reducing volume and speed of traffic and providing segregated infrastructure such as cycle lanes are associated with increased physical activity through cycling 38. Reducing the size of wine glasses and wine bottles reduces alcohol consumption 3940…”
Section: Tackling Behavioural and Social Causes In Parallelmentioning
confidence: 99%